Disrupted Rhythmicity and Vegetative Functions Relate to PTSD and Gender in Earthquake Survivors - Carmassi, Claudia; Dell'Oste, Valerio; Bertelloni, Carlo Antonio; Foghi, Claudia; Diadema, Elisa; Mucci, Federico; Massimetti, Gabriele; Rossi, Alessandro; Dell'Osso, Liliana (Frontiers in Psychiatry, 2020)
Background: Increasing evidence indicates that survivors to traumatic events may show disruption of sleep pattern, eating and sexual behaviors, as well as somatic symptoms suggestive of alterations of bio-rhythmicity and vegetative functions. Therefore, aim of this study was to investigate these possible alterations in a sample of survivors in the aftermath of earthquake exposure, with particular attention to gender differences and impact of post-traumatic stress disorder (PTSD). Methods: High school senior students, who had been exposed to the 2009 L'Aquila earthquake, were enrolled 21 months after the traumatic event and evaluated by the Trauma and Loss Spectrum Self-Report (TALS-SR) to investigate PTSD rates, and by a domain of the Mood Spectrum-Self Report-Lifetime Version (MOODS-SR), to explore alterations in circadian/seasonal rhythms and vegetative functions. Results: The rates of endorsement of MOOD-SR Rhythmicity and vegetative functions domain and subdomain scores were significantly higher in survivors with PTSD with respect to those without it. Amongst all earthquake survivors, women reported higher scores than men on the Rhythmicity and vegetative functions domain and subdomain scores, except for the Rhythmicity and Sexual functions ones. Female survivors without PTSD showed significantly higher scores than men in the Rhythmicity and vegetative functions total scores and the Sleep and Weight and appetite subdomains. Potentially traumatic events burden predicted Rhythmicity and vegetative functions impairment, with a moderation effect of re-experiencing symptoms. Conclusions: We report impairments in rhythmicity, sleep, eating, sexual and somatic health in survivors to a massive earthquake, particularly amongst subjects with PTSD and higher re-experiencing symptoms, with specific gender-related differences. Evaluating symptoms of impaired rhythmicity and vegetative functions seems essential for a more accurate assessment and clinical management of survivors to a mass trauma.